Как вычислить : (6*cos(π/2-t)-8*sin(π+t))/(3*sin(2π-t)+4*cos(1,5*π-

кристина4тина кристина4тина    3   02.09.2019 08:10    0

Ответы
Nic5748796237067736 Nic5748796237067736  06.10.2020 11:30
Воспользуемся формулами приведения:
   cos(π/2 - t) = sint
   sin(π + t) = -sint
   sin(2π - t) = - sint
   cos(1,5π - t) = -sint
и получим:
(6cos(π/2 - t) - 8sin(π + t)) / (3sin(2π - t) + 4cos(1,5π - t)) = (6sint + 8sint) / (-3sint-4sint) = 14sint / (-7sint) = -2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика